2022
DOI: 10.1021/acs.chemmater.2c00107
|View full text |Cite
|
Sign up to set email alerts
|

Polarity and Ferromagnetism in Two-Dimensional Hybrid Copper Perovskites with Chlorinated Aromatic Spacers

Abstract: Two-dimensional (2D) organic–inorganic hybrid copper halide perovskites have drawn tremendous attention as promising multifunctional materials. Herein, by incorporating ortho -, meta -, and para -chlorine substitutions in the benzylamine structure, we first report the influence of positional isomerism on the crystal structures of chlorobenzylammonium copper(II) chloride perovskites A 2 CuCl 4 . 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…[21][22][23] So far, comparatively few works have sought to explore and understand their magnetic properties. [14] Those that have, revealed a rich phenomenology: depending on the transition metal ion (Cu 2+ , [24][25][26][27][28][29][30][31][32][33][34][35][36] Cr 2+ , [13] Mn 2+ , [28,[37][38][39][40][41] Fe 2+ , [42][43][44][45] Co 2+ , [28,46] Ru 3+ , [47] and Mo 3+ [47] ), the HOIP can exhibit ferromagnetic (FM), antiferromagnetic (AFM), coexistence of FM/ AFM, [33] paramagnetic, or no magnetic ordering at all. [47] In contrast, other hybrid perovskite-type magnetic materials such as metal-formates [14,[48][49][50] and hypophosphites [51] have shown less magnetic tunability by chemical design.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] So far, comparatively few works have sought to explore and understand their magnetic properties. [14] Those that have, revealed a rich phenomenology: depending on the transition metal ion (Cu 2+ , [24][25][26][27][28][29][30][31][32][33][34][35][36] Cr 2+ , [13] Mn 2+ , [28,[37][38][39][40][41] Fe 2+ , [42][43][44][45] Co 2+ , [28,46] Ru 3+ , [47] and Mo 3+ [47] ), the HOIP can exhibit ferromagnetic (FM), antiferromagnetic (AFM), coexistence of FM/ AFM, [33] paramagnetic, or no magnetic ordering at all. [47] In contrast, other hybrid perovskite-type magnetic materials such as metal-formates [14,[48][49][50] and hypophosphites [51] have shown less magnetic tunability by chemical design.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in organic–inorganic hybrid (OIH) metal halides has been burgeoning as they have emerged as a forefront candidate for light-harvesting and optoelectronic applications and possess fascinating multifunctional properties like magnetism, ferroelectricity, and so forth. These properties are mainly governed by the crystal structure of these compounds. Especially, the structural dimensionality has a great impact on the photophysical properties . The three-dimensional (3D) hybrid halide perovskites can exhibit long-range carrier transport and low exciton binding energy, hence making them promising materials for solar cells. However, they demonstrate a narrow emission band resulting from free exciton emission and are not compatible for single-component white-light LED applications. , On the other hand, low-dimensional compounds exhibit broader emission bands and higher photoluminescence quantum yield (PLQY) than 3D compounds. Among the low-dimensional materials, the zero-dimensional (0D) compounds exhibit the highest quantum yield due to internal quantum confinement, including the broad emission spectrum. , The broadening of emission linewidth has been attributed to self-trapped exciton (STE) emission. , STEs are transient defect species in the excited state resulting from elastic structural distortion in a soft deformable lattice. , STEs are analogous to Frenkel-like excitons or small polarons with a small exciton Bohr radius. , Therefore, charge carrier localization is imperative for STE emission, which is achieved in 0D compounds. , In such a low-dimensional lattice, the photoexcited charge carriers are stabilized by strong electron–phonon coupling .…”
Section: Introductionmentioning
confidence: 99%
“…Among 2D HOIHs Cu(II)-based ones have lately shown considerable potential, as it was demonstrated that they can be considered as equally efficient but environmentally more benign options to the Pb-based HOIHs which were typically engaged in photovoltaic applications [ 16 , 17 ]. On the other hand, Cu(II)-based HOIHs can display different magnetic-based phenomena like chiral ferromagnetism or multiferroic behavior [ 18 , 19 , 20 , 21 ], along with the stimuli-responsive behavior like thermochromism [ 22 , 23 , 24 , 25 , 26 , 27 ], which extends the paths of their application. While trying to comprehend the intimate structure–property relationship in HOIHs, one becomes aware of a multitude of factors that are coupled with the particular structural type, and subsequently its properties and potential for application.…”
Section: Introductionmentioning
confidence: 99%